KINERJA GURU TERSERTIFIKASI DALAM MENINGKATKAN PRESTASI SISWA DI SMK NEGERI 2 SUKOHARJO - Sri Riris Sugiyarti, Rizki May Suwandani, Aris Tri Haryanto & (Transformasi, 2016)
The purpose of this study was to measure the performance of certified teachers at SMKNegeri 2 Sukoharjo using relevant indicators object diteliti.Selain the facilities andinfrastructure available at SMK Negeri 2 Sukoharjo also be a supporting part in supporting theperformance of teachers in the school. Assessment of students also became one of the factorsthat successfully supporting the performance of the certified teachers.Keywords: Organization, Teacher Work and Management Work